Problem-based learning in calculus course: Perception, engagement and performance - Mokhtar M.Z.; Tarmizi M.A.A.; Tarmizi R.A.; Ayub A.F.M. (2023)
Calculus is an important subject for science and engineering students but phenomenally it is abstract, difficult and highly boring. Hence, problem-based learning (PBL) which adopted a student-centered and active learning approach can be used to improve students' participation, interests and performance in learning of calculus. This study is designed to investigate: (1) student's perception about PBL approach in calculus; (2) student's engagement during the acquisition of understanding of calculus and; (3) student's performance as a result of PBL learning experience. A group of 24 Foundation Year students was randomly selected to undergo the PBL approach in Basic Calculus course. A rubric-scoring assessment was used to evaluate students engagement level, a questionnaire with open ended question was used to assess students' perception of PBL learning, and a post-test to measure students' performance after undergoing PBL approach. This pedagogical approach has made the teaching and learning of calculus more interesting and effective. It is also able to develop the potential of individuals to be more creative, critical in their thinking and effective in problem solving.